Preclinical characterization of Sintilimab, a fully human anti-PD-1 therapeutic monoclonal antibody for cancer. (5th September 2018) - Zhang, Shuang; Zhang, Min; Wu, Weiwei; Yuan, Zhijun; Tsun, Andy; Wu, Min; Chen, Bingliang; Li, Jia; Miao, Xiaoniu; Miao, Xiaoliang; Liu, Xiaolin; Yu, Dechao; et al.
ABSTRACT: Background: Programmed cell death 1 (PD-1) is an inhibitory immune checkpoint expressed on activatedT cells. Upon the formation of T cell receptor (TCR)-pMHC complexes, concomitant PD-1 ligation to its ligands programmed death-ligand 1 (PD-L1) or programmed death-ligand 2 (PD-L2) downregulates TCR signaling and effector function. Here we describe the preclinical characterization of Sintilimab, a fully human IgG4 antibody that potently blocks PD-1 interactions with PD-L1 and PD-L2. Methods: The binding affinity and blockade function were detected by using surface plasmon resonance (SPR), Enzyme-linked immunosorbent assay (ELISA) and flow cytometry. The biology function properties were measured with luciferase assay and mixed lymphocyte reaction assay. In vivo anti-tumor function and preclinical pharmacokinetic (PK) were identified with human PD-1 transgenic mice and non-human primates separately. Results: Sintilimab can specifically and strongly bind to human PD-1 (hPD-1) and cynomolgus PD-1 and the affinity of Sintilimab to human PD-1 was measured at 0.3 nm via surface SPR, and displayed slow dissociation kinetics. Sintilimab can block the interaction of PD-1 to PD-L1 and PD-L2 and induce high secretion levels of interferon (IFN)-γ and interleukin (IL)-2 in primary T cell assays. In humanized hPD-1 knock-in mouse models, Sintilimab showed potent anti-tumor activity and increased tumor-infiltrating CD8/CD4 T cell and CD8/ Treg ratios. Preclinical experimentation in non-human primates following a single intravenous infusion of Sintilimab at 1, 6 and 30 mg/kg presented with no signs of drug-related toxicity, and showed typical PK characteristics of an IgG antibody. Conclusions: Sintilimab has desirable preclinical attributes that supports its clinical development for cancer treatment.